Experimental infection and horizontal transmission of Bartonella henselae in domestic cats - Marcelo de Souza ZANUTTO; Elza Masae MAMIZUKA; Roberto RAIZ-JÚNIOR; Thais Martins de LIMA; Constância Lima DIOGO; Thelma Suely OKAY; Mitika Kuribayashi HAGIWARA (Revista do Instituto de Medicina Tropical de São Paulo, 2001)
In order to study B. henselae transmission among cats, five young cats were kept in confinement for two years, one of them being inoculated by SC route with B. henselae (10(5) UFC). Only occasional contact among cats occurred but the presence of fleas was observed in all animals throughout the period. Blood culture for isolation of bacteria, PCR-HSP and FTSZ (gender specific), and BH-PCR (species-specific), as well as indirect immunofluorescence method for anti-B. henselae antibodies were performed to confirm the infection of the inoculated cat as well as the other naive cats. Considering the inoculated animal, B. henselae was first isolated by blood culture two months after inoculation, bacteremia last for four months, the specific antibodies being detected by IFI during the entire period. All contacting animals presented with bacteremia 6 months after experimental inoculation but IFI did not detect seroconversion in these animals. All the isolates from these cats were characterized as Bartonella (HSP and FTSZ-PCR), henselae (BH-PCR). However, DNA of B. henselae could not be amplified directly from peripheral blood by the PCR protocols used. Isolation of bacteria by blood culture was the most efficient method to diagnose infection compared to PCR or IFI. The role of fleas in the epidemiology of B. henselae infection in cats is discussed.